2016
DOI: 10.1103/physreva.93.053827
|View full text |Cite
|
Sign up to set email alerts
|

Response of a mechanical oscillator in an optomechanical cavity driven by a finite-bandwidth squeezed vacuum excitation

Abstract: In this paper, we theoretically investigate the displacement and momentum fluctuations spectra of the movable mirror in a standard optomechanical system driven by a finite-bandwidth squeezed vacuum light accompanying a coherent laser field. Two cases in which the squeezed vacuum is generated by degenerated and non-degenerate parametric oscillators (DPO and NDPO) are considered. We find that for the case of finite-bandwidth squeezed vacuum injection, the two spectra exhibit unique features, which strongly diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Squeezed bath -We now generalize the above results to the case of a bosonic mode subject to a non-equilibrium broadband squeezed bath. This type of reservoir appears frequently in quantum optics [14,[33][34][35][36][37], whenever the squeeze radiation field is treated as an external bath. The bath is characterized by a temperature T (usually zero), a squeeze parameters re iθ and a central frequency ω s , related to the production of the squeezed field (usually by parametric down conversion).…”
mentioning
confidence: 99%
“…Squeezed bath -We now generalize the above results to the case of a bosonic mode subject to a non-equilibrium broadband squeezed bath. This type of reservoir appears frequently in quantum optics [14,[33][34][35][36][37], whenever the squeeze radiation field is treated as an external bath. The bath is characterized by a temperature T (usually zero), a squeeze parameters re iθ and a central frequency ω s , related to the production of the squeezed field (usually by parametric down conversion).…”
mentioning
confidence: 99%
“…Also, it has been recently theoretically shown that even the intracavity squeezing generated by parametric down conversion can enhance quantum-limited optomechanical position detection through de-amplification 219 . More recently, by investigating the response of the MO in an optomechanical cavity driven by a squeezed vacuum it has been shown that the system can be used as a high sensitive nonclassical light sensor 220 . In this section, we show that in the presence of CQNC if the cavity mode is injected with squeezed light with an appropriate phase, BA noise cancellation provided by CQNC is much more effective because squeezing allows to suppress the SN contribution at a much smaller input power, and one has a significant reduction of the force noise spectrum even with moderate values of squeezing and input laser power.…”
Section: Coherent Quantum Noise Cancellation (Cqnc): Destructive Quan...mentioning
confidence: 99%
“…highly sensitive measurements of physical parameters using a non-classical state of light [2][3][4][5]. The overcoming limitations for sensing hold relevance to biophysical and medical applications where sensitivity and resolution have a central role in the diagnosis [1].…”
Section: Introductionmentioning
confidence: 99%